The development of women's soccer legacies, participation and popularity in Germany - Meier, Henk Erik 1972- (Routledge, 2020)
Germany as a natural experiment for the future of women's soccer -- The development of girls' and women's grassroots soccer -- Stadium attendance in women's league soccer -- The popularity of the women's national soccer team -- How female will the future of soccer be?
Keywords: Frauenfußball; Deutschland; Soccer for women / History / Germany; Soccer for women / Social aspects; Feminism and sports; Soccer / History; Soccer / Social aspects; Soccer players / United States; Soccer players / Germany; Feminism / Germany; Language and culture; Soccer for women; Germany; History; Soccer for women; Social aspects; Soccer; History; Soccer; Social aspects; Soccer players; United States; Soccer players; Germany; Feminism; Germany; SPORTS & RECREATION / Soccer; bisacsh; SPORTS & RECREATION / Sociology of Sports; bisacsh